Platelet Aggregation by Thimerosal - Leone, G; Boni, P; Vincenti, A (Thrombosis and Haemostasis, 1976)
Thimerosal, a sulphydryl inhibitor, induces aggregation of normal platelet rich plasma over a wide range of concentrations. Low doses induce a monophasic response preceded by a lag phase, high doses produce an immediate biphasic response.Thimerosal induces platelet aggregation through its binding by sulphydryl groups.Thimerosal induced aggregation is not mediated by ADP, it is not influenced by fibrinogen, von Willebrand factor, calcium, and magnesium ions of the medium.Thimerosal induced platelet aggregation is normal in patients affected by thrombocyto-pathia (defect of ADP release) but not in patients affected by Glanzmann’s thrombasthenia. Mercaptopropionglycine, a substance which tends to preserve SH groups, inhibits platelet aggregation induced by thimerosal, thrombin, collagen, and ADP.A mechanism is proposed for thimerosal induced aggregation and the role of SH groups also in ADP, thrombin and collagen induced aggregation is indicated.